RETHINKING LEGALITY OF STATE RESPONSIBILITY ON CLIMATE CHANGE IN INTERNATIONAL LAW PERSPECTIVES - Mada Apriandi Zuhir (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Each state has sovereign right to explore and exploit their natural resources, however, it is also followed by state responsibility. This article examines the regime of state responsibility and the regime of climate change. State responsibility is applied to examine the implementation of international law toward climate change issues. This is a normative-juridical research by applying analytical descriptive approach. In the meantime, main data are secondary data (primary, secondary and tertiary legal materials). Then, the data were qualitatively analyzed. Based on the discussion it can be concluded that the regime of state responsibility in international law can be applied to the issue of climate change although this regime has limitations in its implementation. Therefore, it is advisable to have an independent and specific regime related to the state responsibility on climate change issues.Keywords: International law, climate change, state responsibility